Appropriate Self-Perceived Behaviors in Primary Education Pupils During Sports Games - Gil-Madrona, Pedro; Gómez, José Luis; Aguilar-Jurado, Miguel Ángel; Gutiérrez-Marín, Eva Cristina (Frontiers in Psychology, 2020)
Based on the results obtained from Primary Education students—fifth and sixth graders—the aim of this work is to check the appropriate self-perceived behaviours during and at the end of the game. The study population was made up of 698 students from fifth and sixth grade in the Autonomous Region of Castilla-La Mancha (Spain). Data was collected through a questionnaire (scale) on the social skills of Primary School students linked to the adequate skills when losing, the adequate skills when winning, the adequate skills during the game. Study results revealed that analysed behaviours vary depending on the moment of the game, being it more frequently during the development of the game than when losing or winning.